Recent collections of Sergentomyia squamirostris (Diptera: Psychodidae) in Japan, with descriptions and illustrations - SANJOBA, Chizu; ÖZBEL, Yusuf; ASADA, Masahito; MATSUMOTO, Yoshitsugu; OSADA, Yasutaka; GANTUYA, Sambuu (Medical Entomology and Zoology, 2011)
Sergentomyia squamirostris was collected from Akita, Gunma, and Tottori prefectures in Japan. These are the first distributional records of S. squamirostris from Akita and Tottori prefectures. Detailed descriptions and illustrations of genital pump, paramere, aedeagus, surstyle, and the heads of male and female S. squamirostris collected in Japan are presented for the first time.